Laws on e-commerce / edited by S.R.Sharma - Sharma,S.r.(ed.) (New Delhi, 2004)
This book provides an elaborate discussion centering on the major topics like The Internet: An Introduction; On-Line Marketing; The Law Firm Intranet; Knowledge Management and Intranets; Electronic Commerce; Legal Electronic Commerce; On-Line Practicalities; Web Technology; Security and the Internet; E- Commerce: Proposed Legal Framework; UNCITRAL Model Law on Electronic Commerce; and Cyber Crime in India etc.
Keywords: Cyber crime